Analysis of marine propeller using computational fluid dynamics. (2022) - Vimala, V.; Veeramanikandan, K.; Viswanathan, N.; Pitchia Krishnan, B.; Hari, S.; Madhavan, S.; Dhinesh, S.; Karthikeyan, V.
Abstract: This project aims at improving the performance of a marine propeller by varying the velocity at different condition. Solid work software is used for designing the marine propeller and the analysis is carried out in ANSYS fluent software using Computational Fluid Dynamics (CFD) methodology. The results of pressure, velocity and turbulence are obtained and the optimized rotational velocity has been determined.